STUDI PENCIPTAAN KARYA SENIRUPA WAYANG BEBER MENGGUNAKAN TEKNIK KOLASE DENGAN MEMANFAATKAN KORAN BEKAS - Zarkasi, Much Sofwan (Acintya, 2010)
Research on the creation of works of art entitled The Creation Studies of Fine Art on Wayang Beber Using Collage Techniques by Utilizing Newspapers, in 2011 by Much. Sofwan Zarkasi aims to open up wide and open opportunities related to creativity in traditional art and in an increasingly globalized environment. It also creates works of art on Beber puppets using collage techniques and newsprint as an alternative form in viewing works of art on Beber puppet that has used paint manufacturer with natural dyes and painting techniques. The creation of art works on beber puppets with collages technique using newspapers is an engineering development that is undertaken in the work of art of collage using feathers (hair painting) and collage using banana tree bark. The novelty of the study on the creation of arts works in this research is on visual form and technique that has been there in the beber puppet that is using decoration techniques, natural dyes and the manufacturer. The research is the creation of works of art on beber puppet made by collage technique using glue and old newspapers and not using any dyes. The method applied in the creation of the work on this research is a method of experimentation that is the process of conducting experiments put forward from designing plan, preparation and realization of the work in the media. Keywords: Beber puppet, technique, modes of creation,Â experimental method,Â